Banking ecosystems: Identification latent innovation opportunities increasing their long-term competitiveness based on a model the technological increment - Yana S. Matkovskaya; Elena Vechkinzova; Valeriy Biryukov (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Ecosystem business models are becoming widespread in the modern economy; their potential is increasingly understood by financial institutions. Banks become part of the ecosystems and some of them initiate their creation, seeing in this business model an opportunity for their development. However, not all the possibilities of the ecosystem business model are sufficiently recognized by banks. Meanwhile, becoming "orchestrators" of ecosystems, banks get new opportunities, taking on new management functions that require the development of new promising competencies. This aspect predetermined the goal of this article-to explore the essence and development prospects of banking ecosystems and create a model for the establishment of additional innovative and technological advantages for banking ecosystems, allowing the bank to create conditions for long-term competitive advantages. Methods of comparative analysis, statistical methods, modeling methods, and cluster and regression analysis were applied. The results: a model of technological increment that formed during the functioning of the banking ecosystem has been developed; the authors established that the orchestration of the ecosystem by the bank creates opportunities for the formation of new profit centers because of the formation's greater number of innovative technologies and the possibility to dispose the intellectual property.
Keywords: 650; banking ecosystems; ecosystem business models; innovative technologies; orchestrating of ecosystems